The level of school culture and school innovativeness practiced among national type Tamil primary schools - Selvaraja, Kavitha; Lope Pihie, Zaidatol Akmaliah (International Journal of Innovative Research in Technology & Science (IJIRTS), 2016)
The purpose of this study is to identify the level of school culture and school innovativeness practiced among Tamil primary schools,in Kuala Langat, Selangor, Malaysia.Nine Tamil primary schools were selected using cluster sampling. All the teachers in the sample schools were selected to participate in the study. A total of 177 teachers from nine Tamil primary schools were selected to participate in the study. Organizational Culture Assessment Instrument (OCAI) was used to measure school culture whereas Public School Entrepreneurship Inventory (PSEI) was used to measure school innovativeness. The instruments give high Cronbach’s Alpha values which is 0.952 and 0.925 for the culture and innovativeness dimensions, respectively. Descriptive statistics was used to analyze the primary data gathered through survey method. The result shows that Tamil primary schools, in Kuala Langat, Selangor practice clan culture and show less interest in adhocracy culture. Moreover, Tamil primary schools also implement innovativeness with moderate level.